2003
DOI: 10.1128/aem.69.12.7124-7129.2003
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of Geobacillus stearothermophilus Spores by High-Pressure CarbonDioxideTreatment

Abstract: High-pressure CO 2 treatment has been studied as a promising method for inactivating bacterial spores. In the present study, we compared this method with other sterilization techniques, including heat and pressure treatment. Spores of Bacillus coagulans, Bacillus subtilis, Bacillus cereus, Bacillus licheniformis, and Geobacillus stearothermophilus were subjected to CO 2 treatment at 30 MPa and 35°C, to high-hydrostatic-pressure treatment at 200 MPa and 65°C, or to heat treatment at 0.1 MPa and 85°C. All of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(55 citation statements)
references
References 27 publications
2
50
0
2
Order By: Relevance
“…Treatment efficiency can be proved by the release of DPA to the suspension after the alkaline treatment and TEM observations. It has been previously reported that inactivation of G. stearothermophilus at low temperatures (<100 o C) can be achieved using chemicals agents (Mazzola et al, 2003;Rogers et al, 2007), high-pressure carbon dioxide (Watanabe et al, 2003) and supercritical carbon dioxide with added hydrogen peroxide (Hemmer et al, 2007) but the time required to inactivate spores is high. The D-values found in literature for inactivation assays carried out at temperature 100 o C were higher than those obtained in this work (Table S1), except when using high pressure treatments (Patazca et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Treatment efficiency can be proved by the release of DPA to the suspension after the alkaline treatment and TEM observations. It has been previously reported that inactivation of G. stearothermophilus at low temperatures (<100 o C) can be achieved using chemicals agents (Mazzola et al, 2003;Rogers et al, 2007), high-pressure carbon dioxide (Watanabe et al, 2003) and supercritical carbon dioxide with added hydrogen peroxide (Hemmer et al, 2007) but the time required to inactivate spores is high. The D-values found in literature for inactivation assays carried out at temperature 100 o C were higher than those obtained in this work (Table S1), except when using high pressure treatments (Patazca et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the low water content in the core and the intrinsic thermostability of proteins confers to spores of thermophilic species a higher resistant to wet heat than to those of mesophiles (Guizelini et al, 2012). Therefore, the spores of this organism are often used as a biological indicator to assess the effectiveness of sterilization methods (Lo 'pez et al, 1997;Watanabe et al, 2003;Wood et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The inoculated media was immediately placed in a 4 L pressure vessel (Alloy Products Corp, Waukesha, WI) and made anaerobic through the use of a GasPak ™ EZ Anaerobe Container System Sachet (BD, Franklin Lakes, NJ).The serum bottles in the vessels were then pressurized to 1.0 MPa in the field with ultrapure CO 2 . Previous work has shown that CO 2 is very effective sterilant (Nakamura et al, 1994;Isenschmid et al, 1995;Ballestra et al, 1996;Shimoda et al, 1998;Hong and Pyun, 1999;Erkmen, 2000;Spilimbergo and Bertucco, 2003;Watanabe et al, 2003;Damar and Balaban, 2006;Oule et al, 2006Oule et al, , 2010Song et al, 2007). With this in mind, we reasoned that cultures grown at very high CO 2 pressures would likely result in a sterilization of most viable microorganisms, especially those accidentally introduced through contamination.…”
Section: Field Samplingmentioning
confidence: 99%
“…CO 2 will reside in the reservoir as a plume of supercritical fluid and will gradually dissolve into the water. Given that high aqueous CO 2 concentrations are generally toxic to most microorganisms as the molecule interferes with intracellular functions (Hong and Pyun, 1999;Spilimbergo and Bertucco, 2003;Watanabe et al, 2003;Damar and Balaban, 2006;Mitchell et al, 2008;Santillan et al, 2013), this change will initially stress the native microbial population. However, over longer time scales, these new conditions may create a niche for CO 2 -tolerant bacteria that will select for a new community of microorganisms capable of resisting CO 2 toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…W literaturze pojawiają się jednak prace związane z zastosowaniem tego czynnika zarówno w stanie nadkrytycznym, jak i w stanie gazowym pod wysokim ciśnieniem do inaktywacji mikroorganizmów: bakterii patogennych przenoszonych przez żywność, m.in. Escherichia coli, Salmonella spp., Listeria monocytogenes, Staphylococcus aureus oraz drożdży, pleśni i bakterii fermentacji mlekowej w przetworach owocowo-warzywnych [4, 6, 7, 17, 27, 28,], a także do inaktywacji przetrwalników [5,8,29], w tym A. acidoterrestris [1,3].…”
Section: Wprowadzenieunclassified